e-Science and its application: life sciences and finance - Perrott, R. H. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2005)
In 2001, the UK government announced new funding for an initiative known as e-Science. This initiative was challenged with developing a new way of collaborative research using grid as the information utility. The initiative was structured to provide funding to support a national grid infrastructure, tackle large scale scientific research problems and to engage in projects with industry. This paper considers the impact of e-Science in the UK and, in particular, in the finance and life sciences sectors.